2021
DOI: 10.1002/asia.202100829
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cyclization of 1,n‐Enynes and 1,n‐Dienes for the Synthesis of 2‐Pyrrolidone

Abstract: 2‐Pyrrolidones have aroused enormous interest as a useful structural moiety in drug discovery; however, not only does their syntheses suffer from low selectivity and yield, but also it requires high catalyst loadings. The radical cyclization of 1,n‐enynes and 1,n‐dienes has demonstrated to be an attractive method for the synthesis of 2‐pyrrolidones due to its mild reaction conditions, fewer steps, higher atom economy, excellent functional group compatibility, and high regioselectivity. Furthermore, radical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 123 publications
0
14
0
Order By: Relevance
“…The reaction smoothly produced desired products with terminal alkyne ( 4 a ) in 58 % yield. But, we observed mixture of E / Z (15 : 85 ratio) isomers due to no steric effect in the vinyl radical intermediate ( B ) for incoming iodine radical [2a] . The reaction smoothly produced desired products with internal alkyne with R 1 bearing electron‐donating groups such as −Ph ( 4 aa ) m ‐Me−Ph ( 4 ba , E / Z =13 : 87), p ‐Me−Ph ( 4 ca ), and p ‐OMe−Ph ( 4 da , E / Z =5 : 95) to afford a highly substituted sulfone/active C−I bond bearing pyrrolidine derivatives in excellent yields (72–85 %) without effecting the electron‐donating ability of the functional group on aromatic.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The reaction smoothly produced desired products with terminal alkyne ( 4 a ) in 58 % yield. But, we observed mixture of E / Z (15 : 85 ratio) isomers due to no steric effect in the vinyl radical intermediate ( B ) for incoming iodine radical [2a] . The reaction smoothly produced desired products with internal alkyne with R 1 bearing electron‐donating groups such as −Ph ( 4 aa ) m ‐Me−Ph ( 4 ba , E / Z =13 : 87), p ‐Me−Ph ( 4 ca ), and p ‐OMe−Ph ( 4 da , E / Z =5 : 95) to afford a highly substituted sulfone/active C−I bond bearing pyrrolidine derivatives in excellent yields (72–85 %) without effecting the electron‐donating ability of the functional group on aromatic.…”
Section: Resultsmentioning
confidence: 73%
“…However, we observed mixture of E / Z isomers (50 : 50) in the product. The anticipated reason could be a less steric effect of the methyl group for incoming iodine [2a] . The radical sensitive −TMS group smoothly delivered the desired product ( 4 ha ) in moderate yield (61 %).…”
Section: Resultsmentioning
confidence: 99%
“…1, n -Dienes are frequently used as radical receptors, which are susceptible to being attacked by foreign radicals and undergo radical cyclization reactions to establish cyclic frameworks concisely and effectively. 19 In 2021, Li, Wei and their colleagues proposed an iodosulfonylation/bicyclization of 1,6-dienes initiated by the sulfonyl radical (Scheme 6). 20 This strategy showed that cyclization products were obtained when the sulfonyl radical provided two targeted function sites, and it is worth noting that five-membered iodosulfonation products could be obtained when there was a source of iodine in the system.…”
Section: Sulfonyl Hydrazides As Sulfonyl Radicalsmentioning
confidence: 99%
“…1). 2 In this regard, this privileged motif has gained considerable attention for the expansion of novel synthetic methodologies. 3 Among them, free radical tandem cyclization has emerged as one of the strategically efficient and synthetically useful protocols for the construction of five membered frameworks (Fig.…”
mentioning
confidence: 99%